Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012 13th International Thermal, Mechanical and Multi-Physics Simulation and Experiments in Microelectronics and Microsystems 2012
DOI: 10.1109/esime.2012.6191762
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of thermo-mechanical stresses in Low Temperature Joining Technology

Abstract: The Low Temperature Joining Technology (L T JT) creates silver joints by a sintering process. It is an alternative die-attach technology to soldering. To initiate the sintering process the temperature has to be raised above � 215°C. The quality of a sintered joint is strongly enhanced by applying pressure to the specimen during the process, thus reducing the porosity in the sintered material. After the interconnect process, residual stresses occur in the sintered material, as well as in the joined parts.The ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 5 publications
0
24
0
Order By: Relevance
“…This simple correlation may be flawed, however, as high-strength materials typically have low fracture toughness, which is a measure of the resistance to crack growth during cyclic loading. 74 Another explanation for this observation in Table III is that the sintered nano-Ag joints had a higher density than the micron-Ag joints, although this postulate cannot be confirmed because the density for the micron Ag joints was not reported, 63 while the density for the nano-Ag joints was only 80.4 %. 64 In a related study, Suganuma and coworkers 66 researched the influence of Ag-filler shapes on the thermal-fatigue resistance of sintered Ag joints.…”
Section: Density Of Sintered Ag Jointsmentioning
confidence: 56%
See 4 more Smart Citations
“…This simple correlation may be flawed, however, as high-strength materials typically have low fracture toughness, which is a measure of the resistance to crack growth during cyclic loading. 74 Another explanation for this observation in Table III is that the sintered nano-Ag joints had a higher density than the micron-Ag joints, although this postulate cannot be confirmed because the density for the micron Ag joints was not reported, 63 while the density for the nano-Ag joints was only 80.4 %. 64 In a related study, Suganuma and coworkers 66 researched the influence of Ag-filler shapes on the thermal-fatigue resistance of sintered Ag joints.…”
Section: Density Of Sintered Ag Jointsmentioning
confidence: 56%
“…It has been reported that the die-attach thickness plays a more crucial role than the die size in thermal life-cycle studies of sintered Ag joints 63 because different ''stress-relief'' mechanisms predominate at different die-attach thicknesses. 71 According to that study, sintered Ag joints were found to be unsuitable for die-attach thicknesses of 75 lm or more because of their increased propensity for crack growth instead of stress relaxation within the sintered Ag layer.…”
Section: Interfacial Characteristics Of Sintered Ag Jointsmentioning
confidence: 99%
See 3 more Smart Citations